The Electromagnetic Scattering Problem by a Cylindrical Doubly-Connected Domain at Oblique Incidence: An Inverse Problem - Mindrinos, Leonidas (Journal of Advances in Applied & Computational Mathematics, 2023)
In this work, we examine the inverse problem to reconstruct the inner boundary of a cylindrical doubly-connected infinitely long medium from measurements of the scattered electromagnetic wave in the far-field. We consider the integral representation of the solution to derive a non-linear system of equations for the unknown radial function. We propose an iterative scheme using linearization and regularization techniques.